Taxonomic description and 3D modelling of a new species of myzostomid (Annelida, Myzostomida) associated with black corals from Madagascar - Terrana, Lucas; Eeckhaut, Igor (Zootaxa, 2017)
Eenymeenymyzostoma nigrocorallium n. sp. is the first species of myzostomid worm associated with black corals to be described. Endoparasitic specimens of E. nigrocorallium were found associated with three species of antipatharians on the Great Reef of Toliara. Individuals inhabit the gastrovascular ducts of their hosts and evidence of infestation is, most of the time, not visible externally. Phylogenetic analyses based on 18S rDNA, 16S rDNA and COI data indicate a close relation to Eenymeenymyzostoma cirripedium, the only other species of the genus. The morphology of E. nigrocorallium is very unusual compared to that of the more conventional E. cirripedium. The new species has five pairs of extremely reduced parapodia located on the body margin and no introvert, cirri or lateral organs. Individuals are hermaphroditic, with the male and female gonads both being located dorsally in the trunk. It also has a highly developed parenchymo-muscular layer on the ventral side, and the digestive system lies in the middle part of the trunk. A three-dimensional digital model of this worm’s body plan has been constructed whereby the external morphology and in toto views of the observed organ systems (nervous, digestive and reproductive) can be viewed on-screen: http://doi.org/10.13140/RG.2.2.17911.21923.